A Comparative Analysis of FBD, PQ and CPT Current Decompositions - Part II: Three-Phase Four-Wire Systems - Paredes, Helmo K. M.; Marafao, Fernando P. [UNESP]; Silva, Luiz C. P. da; Toma, L.; Otomega, B. (Ieee, 2009)
This paper investigates the major similarities and discrepancies among three important current decompositions proposed for the interpretation of unbalanced and/or non linear three-phase four-wire power circuits. The considered approaches were the so-called FBD Theory, the pq-Theory and the CPT. Although the methods are based on different concepts, the results obtained under ideal conditions (sinusoidal and balanced signals) are very similar. The main differences appear in the presence of unbalanced and non linear load conditions. It will be demonstrated and discussed how the choice of the voltage referential and the return conductor impedance can influence in the resulting current components, as well as, the way of interpreting a power circuit with return conductor. Under linear unbalanced conditions, both FBI) and pq-Theory suggest that the some current components contain a third-order harmonic. Besides, neither pq-Theory nor FBI) method are able to provide accurate information for reactive current under unbalanced and distorted conditions, what can he done by means of the CPT.
Keywords: FBD-theory; pq-theory; Homo-variables; harmonics; current decomposition; power theory